DIGITAL SOLUTIONS IN THE MINING AND METALLURGICAL SECTOR OF KAZAKHSTAN - Balakan, Islam; Aubakirova, Gulnara; Issatayeva, Farida (SWorld-Ger Conference proceedings, 2025)
The relevance of the study is dictated by the increasing role of mining metallurgical sector of Kazakhstan in the energy transition. The authors substantiate the feasibility digitalization mountain-metallurgical sector to improve the assessment of the im